2021
DOI: 10.3390/ijerph18105097
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Community-Based Options for Reducing Youth Crime

Abstract: BackTrack is a multi-component, community-based intervention designed to build capacity amongst 14–17-year-old high risk young people. The aim of the current study seeks to explore community value and preferences for reducing youth crime and improving community safety using BackTrack in a rural setting in Armidale, New South Wales, Australia. The study design used discrete choice experiments (DCEs), designed in accordance with the 10-item checklist outlined by the International Society for Pharmacoeconomics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In the BackTrack DCE, participants were asked to choose between BackTrack and a policing alternative, with different costs and efficacies. The full methods and results of the DCE are published elsewhere [ 23 ]. The results of the DCE lend support for community preference for community-based interventions like BackTrack compared to a greater police presence, and valued the intervention at (AUD) $150 per household.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the BackTrack DCE, participants were asked to choose between BackTrack and a policing alternative, with different costs and efficacies. The full methods and results of the DCE are published elsewhere [ 23 ]. The results of the DCE lend support for community preference for community-based interventions like BackTrack compared to a greater police presence, and valued the intervention at (AUD) $150 per household.…”
Section: Resultsmentioning
confidence: 99%
“…A Discrete Choice Experiment (DCE) was used to quantify, in monetary terms, the value that households in the BackTrack community placed on improving outcomes for young people with multiple and complex needs [ 23 ]. DCEs involved the use of a survey to systematically quantify individuals’ preferences in relation to a number of characteristics (attributes) of a program [ 24 , 25 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Attaching a value to community benefit is seen as a valuable input in economic evaluations that adopt a social perspective [41]. A recent study by Edmunds et al (2021) used discrete choice experiments to explore community value and preferences for reducing youth crime and improving community safety using BackTrack [42]. The BackTrack program is a multicomponent community intervention targeting 14-17-year-old high risk young people [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Edmunds et al (2021) used discrete choice experiments to explore community value and preferences for reducing youth crime and improving community safety using BackTrack [42]. The BackTrack program is a multicomponent community intervention targeting 14-17-year-old high risk young people [42][43][44]. The authors found a strong community preference for youth based programs such as BackTrack that are community based rather than traditional means of dealing with youth crime through punitive measures [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation